Ceo's networks and companies' performance: evidence from Malaysia - Wong, Voon Leong (2018)
This study seeks to examine the relationship among CEO's networks and companies' performance. Accordingly, two contradicting theories are rooted in this study that estimates the opposing results respectively. In proportion to social network theory, some would predict a positive linkage between the CEO's networks and performance of entities; whereas the agency theory anticipates a negative relationship exist in the CEO's networks and financial performance of the companies. Derived from the measures that employed in this study to evaluate the CEO's networks effect, the empirical results for 100 non-financial companies in Malaysia suggest that CEOs with longer tenure build stronger networking and the companies with large board size are keenly looking for CEOs with an outsized social network. As well, it is observed that the CEO's networks have significant effect on companies' performance particularly sales growths in positive manner. However, neither any significant relationship can be observed between the CEO's networks and return on assets. Lastly, some facts are able to ascertain in Malaysia context for the argument that better-connected CEOs delivery value to companies performance in the course of their social network as consistent with social network theory. In future study, it is suggested to employ different and large sample size in same setting, or different site location in addition to considering different boundary condition of social ties.